Investigating the Effectiveness of Personalized Gamification in Enhancing Student Intrinsic Motivation: an Experimental Study in Real Context - Pereira Júnior, Cleon X.; Santos, Heder Filho S.; Rodrigues, Luiz; Costa, Newarney T. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2023)
Gamification in education has been used to increase student engagement. However, there are concerns about potential negative effects, such as decreased intrinsic motivation and performance. To address these limitations, personalized gamification has emerged as a research focus. It aims to tailor game elements to individual preferences, but its effectiveness compared to a standardized approach is still uncertain. One aspect of personalization that has been underexplored is the visual appearance of game elements. To explore that aspect, we conducted an 4-week experimental study to evaluate gamification personalized through visual appearance in a real lesson context. We focused on the Acknowledgment game element, which is the most used in the literature, and compared students’ learning experiences based on personalized and non-personalized badges. The study presents evidence of the effectiveness of personalizing gamification’s visual appearance in real educational settings, unlike past research that is focused on changing the game elements available. Thus, we reveal the potential of personalizing game elements’ looks to enhance learning experiences.